2010
DOI: 10.1016/j.visres.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Directional processing within the perceptual span during visual target localization

Abstract: In order to understand how processing occurs within the effective field of vision (i.e. perceptual span) during visual target localization, a gaze-contingent moving mask procedure was used to disrupt parafoveal information pickup along the vertical and the horizontal visual fields. When the mask was present within the horizontal visual field, there was a relative increase in saccade probability along the nearby vertical field, but not along the opposite horizontal field. When the mask was present either above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
(78 reference statements)
1
13
0
Order By: Relevance
“…Deubel and Schneider (1996) also showed that it is impossible to discriminate a target at one location while preparing a saccade to another location. Due to this coupling between attention and saccades, saccade amplitudes and direction are thought to reflect attentional selection and thus the spatial extent of parafoveal processing (Greene, Pollatsek, Masserang, Lee, & Rayner, 2010;Loschky & McConkie, 2002;Nuthmann, 2013). Following this notion, the aforementioned effects of central and peripheral scene degradation on saccade amplitudes suggest more focused attention on the unfiltered central region with peripheral filtering and a stronger attentional bias toward the periphery with central filtering.…”
Section: Introductionmentioning
confidence: 99%
“…Deubel and Schneider (1996) also showed that it is impossible to discriminate a target at one location while preparing a saccade to another location. Due to this coupling between attention and saccades, saccade amplitudes and direction are thought to reflect attentional selection and thus the spatial extent of parafoveal processing (Greene, Pollatsek, Masserang, Lee, & Rayner, 2010;Loschky & McConkie, 2002;Nuthmann, 2013). Following this notion, the aforementioned effects of central and peripheral scene degradation on saccade amplitudes suggest more focused attention on the unfiltered central region with peripheral filtering and a stronger attentional bias toward the periphery with central filtering.…”
Section: Introductionmentioning
confidence: 99%
“…In one scene-viewing task, the stimuli were randomly chosen webpages, containing pictures and words. All other stimulus sets are well described in the published datasets ( 45 , 46 , 47 ), and briefly described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Six of the datasets were from 3 published studies that reported the vertical asymmetry in PSFDs during saccadic exploration (Brown & Greene, 2018;Greene & Brown, 2017;Greene et al, 2014). Eight of the datasets were from 3 published studies of saccadic exploration that had not previously checked for the vertical asymmetry in PSFDs (Foulsham & Kingstone, 2010;Greene, Brown, & Paradis, 2013;Greene, Pollatsek, Masserang, Lee, & Rayner, 2010;Strauss, Ossenfort, & Whearty, 2016). Nine new eye-movement datasets were from the laboratories of the authors, and were included in the analysis, to minimize publication bias.…”
Section: Description Of Selected Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when the perceptual span of expert readers is biased towards the direction from which most useful information can be expected (Greene, Pollatsek, Masserang, Ju Lee, & Rayner, 2010; Jordan at al., 2014; Paterson et al, 2014), parafoveal processing of beginning readers is expected to be less biased. However, even though prereaders spend only a small amount of time looking at print in storybooks (Evans & Saint-Aubin, 2005), children in this early stage may, as a result of book-reading experiences and name writing, be familiar with the reading direction of their language (Clay, 1979) and show an asymmetry in the same direction as expert readers.…”
Section: Introductionmentioning
confidence: 99%